Engineering of cell factories for the production of natural products. Issue 9 (10th September 2019) - Weber, Tilmann
Abstract : The Natural Product Reports themed issue on Engineering of cell factories for the production of natural products is introduced by the Guest Editor, Tilmann Weber.